Modal Auxiliaries and Abnormality of Time Reference - Hamoudi , Ali Hindi (International Journal of Psychosocial Rehabilitation, 2020)
The verb phrase is the primary grammatical element where time distinctions are expressed. The time at which an action or event took or takes place is usually indicated by the tense of the verb used, that is, the verb is conjugated according to time. Verb tense is then the indicator of time . In other words, it is the form of the verb that refers to the time of an action or event. The case is different with modal auxiliary verbs in that they do not usually conjugate to show tense and some are defective. Hence, the present study fundamentally tends to shed light on the abnormality of time reference in the use of English modal auxiliary verbs. The concepts of modality, modal verb, time and tense are examined. A collection of example sentences will be discussed as the data for the purpose of showing the time a given modal verb refers to. The study ends up with some concluding remarks to show the abnormality of time reference.